A 10 Year Post Mortem Study of Choking Cases Brought to the Mortuary of a Tertiary Care Hospital in Imphal (Medico Legal Update, 2020)
Choking is the obstruction of air flow into the lungs and is almost always accidental. In this paper, cases ofchoking mistaken to be deaths due to foul play are studied. Any complaint is not true unless it is proved so.In all these cases, family members blamed the deaths on some parties who were in fact completely innocent.Meticulous autopsy helped in establishing the exact cause of death in these cases by disproving the falsecharge of assault. From the legal standpoint, the importance of establishing an exact diagnosis is obvious.